2011
DOI: 10.1007/s11661-011-0760-6
|View full text |Cite
|
Sign up to set email alerts
|

Grain Selection in Spiral Selectors During Investment Casting of Single-Crystal Turbine Blades: Part I. Experimental Investigation

Abstract: Spiral grain selectors are used to grow single-crystal (SX) turbine blades during investment casting. Competitive growth in the spiral selectors leads to the selection of a single grain that subsequently grows to form the blade. In this study, the effect of spiral design on grain selection during investment casting was investigated through a series of experiments. It is found that the spiral design can effectively reduce the grain number but is not able to optimize axial grain orientations during solidificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
44
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(46 citation statements)
references
References 26 publications
2
44
0
Order By: Relevance
“…The remarkable high temperature strength of Ni-base superalloys is derived from the presence of ordered (super-lattice) precipitates, γ / dispersed in a ductile γ matrix and forming a coherent interface [5]. It had been demonstrated that alloys with super-lattice precipitates exhibited superior deformation and creep behaviour compared to either of the constituent phases and which had formed the basis for the design of these alloys [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…The remarkable high temperature strength of Ni-base superalloys is derived from the presence of ordered (super-lattice) precipitates, γ / dispersed in a ductile γ matrix and forming a coherent interface [5]. It had been demonstrated that alloys with super-lattice precipitates exhibited superior deformation and creep behaviour compared to either of the constituent phases and which had formed the basis for the design of these alloys [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Choline chloride [HOC 2 H 4 N(CH 3 ) 3 Cl] (ChCl) (Aldrich 99%) was recrystallized from absolute ethanol, filtered and dried under vacuum. Oxalic acid dihydrate (OXDH) (Aldrich 99%), was used as received.…”
Section: Oxaline 100mentioning
confidence: 99%
“…Typical single crystal superalloys castings are manufactured using the vacuum investment casting process; during this process the molten superalloy is poured in a ceramic mould that has been fabricated via the lost wax method [1][2][3][4][5]. The single crystal growth is controlled in part by the speed and temperature at which this mould is removed from the furnace.…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19] It is important to clarify 3D grain selection behavior for metallurgy applications and directional solidification products, such as turbine blades. [20][21][22] At present, the phase-field method is the only known method for accurately simulating the dendrite structure during solidification. 15,[23][24][25] However, 3D phase-field simulation of multiple dendrites remains a challenging task owing to the high computational cost, in spite of the development of quantitative phase-field models.…”
Section: Introductionmentioning
confidence: 99%